(untitled) (Proceedings of the International Conference on Education, 2021)
First aid training is a fundamental requirement for healthcare programs. For Tec21, there is a week dedicated to educating students in this topic. The COVID-19 pandemic forced the faculty team to redesign the First Aid Week from face-to-face training into a remote learning practice. The purpose was to assess the perceived value of competencies learning, considering first aid emergency skills and interprofessional working. The method was mixed: quantitative with pre-test and post-test (Cronbach alpha 0.93 and 0.97) and qualitative analysis. The difference between expectations (pre-test) vs. achievements(post-test) was analyzed with Expectation Confirmation Theory (Olivares et al., 2019), which classifies results as positive confirmation (+DC), confirmation (C), and negative confirmation (-DC). A total of 253 students participated from Physician and Surgeon, Nutrition and Wellness, Dentistry, Psychology, and Biosciences. Twelve items were related to accident preventive teaching, basic life support, psychological first aid, role designation, and teamwork communication. Day one was about introduction and prevention. On day two, students learned about triage and self-directed group simulation. Third day included a CPR practice (using a DIY mannequin). On day four, students had lectures on psychological first aid and a role-playing activity with peers and instructors. Results indicated +DC on both competencies. Knowledge in practice was 3.34 (±1.13) (pre-test) and 4.84 (±0.57) (post-test) with a p-value of <.0001. Ethical practice and reflection were 4.40 (±0.46) (pre-test) and 4.15 (±0.62) (post-test) with a p-value of 0.025. Interprofessional working was 4.53 (±0.52) (pre-test) and 4.77 (±0.49) (post-test) with a p-value of <.0001. The most common feedback from students was that they learned how to respond in an emergency. Interprofessional Healthcare Education promotes collaboration to enhance the quality of patient care. The distance teaching format was not a barrier to learning. The lack of commercial mannequins was replaced with low-cost simulation activity from home. This innovative immersive week helped students learn about first aid and increase their ability to respond to basic emergencies.